Photophysical and electrochemical studies of highly fluorescent pyrazole and imidazole containing heterocycles. (January 2017) - Maurya, Hardesh K.; Kumar, Ch. Pavan; Chandrasekharam, M.; Gupta, Atul
Abstract: Highly congested pyrazole and imidazole ring containing heterocycles were studied for their photophysical and electrochemical properties. TDDFT calculations of the molecules were carried out using B3LYP/G(d, p) level theory in DMF medium and the results were in good agreement with the experimental values. The imidazole derivatives showed a red shifted absorption peak ( λ max, 455–474 nm) and higher molar extinction coefficient than pyrazole derivatives. In the case of increasing π-conjugation from pyrazoles to imidazoles red shift in the emission maxima (537 nm-565 nm) was observed. These preliminary results of absorption and emission spectroscopy illustrate that these molecules may have potenial for organic applications. Graphical abstract: Highlights: Highly congested pyrazole and imidazole ring containing heterocycles were synthesized. λ max of UV–Vis absorption and photoluminescence (PL) spectra, fluorescence quantum yields of these compounds were studied. HOMO/LUMO energy levels and the electrochemical band gap (Eg) were investigated.